1984
DOI: 10.1071/bi9840163
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Biology of the Booroola Merino Sheep

Abstract: This paper reviews the genetic and physiological characteristics of the Booroola Merino, one of the four most prolific sheep breeds in the world, and which was acquired by CSIRO in 1958 from a commercial sheep property, 'Booroola', Cooma, N.S.W. The exceptional prolificacy of this genotypee.g. mean flock ovulation rate in 1982 of 4·2 (range 1-10) and mean litter size of 2· 5 (range 1-7)-is largely attributable to a single gene (F) of uncertain origin which increases ovulation rate. Crosses of the Booroola wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
3
2

Year Published

1986
1986
1995
1995

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 43 publications
1
59
3
2
Order By: Relevance
“…Follicular response to LH is also acquired in smaller follicles in Booroola ewes compared to Merino ewes (Scaramuzzi, Turnbull, Downing & Bindon, 1981). Furthermore, decreased ovarian inhibin content has been found in Booroola Merino ewes compared to the prolific Merino and control Merino ewes (Cummins, O'Shea, Bindon, Lee & Findlay, 1983;Bindon, 1984). These between-breed and strain differences suggest that each breed might have a different mechanism by which ovulation rate is controlled.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Follicular response to LH is also acquired in smaller follicles in Booroola ewes compared to Merino ewes (Scaramuzzi, Turnbull, Downing & Bindon, 1981). Furthermore, decreased ovarian inhibin content has been found in Booroola Merino ewes compared to the prolific Merino and control Merino ewes (Cummins, O'Shea, Bindon, Lee & Findlay, 1983;Bindon, 1984). These between-breed and strain differences suggest that each breed might have a different mechanism by which ovulation rate is controlled.…”
Section: Introductionmentioning
confidence: 94%
“…There is considerable variation in ovulation rate between breeds of sheep and between strains of sheep within breeds. Despite numerous studies the exact mechanisms which control ovulation rate are still not known (see reviews by Scaramuzzi & Radford, 1983;Webb & Gauld, 1984;Bindon, 1984). A number of follicular characteristics have been associated with higher ovulation rate.…”
Section: Introductionmentioning
confidence: 99%
“…In ram lambs, the effects of the FecBB gene on plasma hormone concentrations are equivocal (Seek el al, 1988;Montgomery et al, 1989;Purvis el al, 1991) and, to our (Bindon, 1984;McNatty et al, 1991aMcNatty et al, , 1992Montgomery el al, 1992 (McNatty et al, 1987a(McNatty et al, , 1989(McNatty et al, , 1993a. In rams, most studies have found no effect of the FecBB gene on plasma FSH and LH concentrations that are independent of sire effects (Bindon et al, 1985(Bindon et al, , 1989Montgomery et al, 1989;Hochereau-de Reviers and Seek, 1991;Price et al, 1991a, b, c;Isaacs et al, 1992 (1982).…”
Section: Introductionmentioning
confidence: 99%
“…Bindon (1984) compared fecund Booroola and normal Merino ewes and concluded that ovulation rate was independent of the amount and pattern of LH secreted in the preovulatory period. Similarly, some researchers examining the nutritional stimulation of ovulation rate have found no effects on pituitary LH content or basal plasma LH concentrations before or after the preovulatory LH surge (Haresign, 1981;Rhind et al, 1984).…”
Section: Introductionmentioning
confidence: 99%